The Role of Financial Performance in Mediating Capital Structure, Ownership Structure on Dividend Policy - Fitriyah, Fitriyah; Nadhiroh, Umi; Restuningdiah, Nurika (MEC-J (Management and Economics Journal), 2024)
This research aims to examine how capital structure and ownership structure affect dividend policy, and to determine if financial performance plays a role in mediating this relationship. The study employs a quantitative methodology alongside an explanatory research technique. The object of this research is Consumer Non-Cyclical sector companies based on the IDX Industrial Classification (IDX-IC). A purposive sampling method was employed to acquire a sample of 28 firms. The technique for analyzing data is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the software WarpPLS 8.0. The results showed that capital structure significantly negatively affects Consumer Non-Cyclical sector companies, with higher debt ratios resulting in lower dividends. Ownership structure also affects dividend policy, with greater share ownership by significant shareholders leading to higher dividends. Financial performance has an effect on dividend policy, suggesting that companies with stable profits have more resources to pay dividends to shareholders. Yet, the financial results cannot act as a mediator for the influence of capital and ownership setups on choices regarding dividends. Future studies need to include different industry sectors to assess uniformity among various economic sectors and address fluctuations in the broader economy.